2019
DOI: 10.1038/s41598-019-54999-x
|View full text |Cite
|
Sign up to set email alerts
|

Nano-encapsulated Escherichia coli Divisome Anchor ZipA, and in Complex with FtsZ

Abstract: The E. coli membrane protein ZipA, binds to the tubulin homologue FtsZ, in the early stage of cell division. We isolated ZipA in a Styrene Maleic Acid lipid particle (SMALP) preserving its position and integrity with native E. coli membrane lipids. Direct binding of ZipA to FtsZ is demonstrated, including FtsZ fibre bundles decorated with ZipA. Using Cryo-Electron Microscopy, small-angle X-ray and neutron scattering, we determine the encapsulated-ZipA structure in isolation, and in complex with FtsZ to a resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 80 publications
(92 reference statements)
3
17
0
Order By: Relevance
“…10B ). This model would be consistent with the cryo-EM structure of full-length ZipA and FtsZ that places the globular domains of both proteins in close contact ( 20 ). Such a two-pronged binding model might also help explain why FtsA, which seemingly interacts only with the FtsZ CTP, has a lower binding affinity for FtsZ than ZipA.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…10B ). This model would be consistent with the cryo-EM structure of full-length ZipA and FtsZ that places the globular domains of both proteins in close contact ( 20 ). Such a two-pronged binding model might also help explain why FtsA, which seemingly interacts only with the FtsZ CTP, has a lower binding affinity for FtsZ than ZipA.…”
Section: Discussionsupporting
confidence: 77%
“…Although a second study showed that oligomerization of FtsZ plays a significant role in strengthening ZipA’s apparent interaction with full-length FtsZ, the possibility of a secondary binding site could not be ruled out ( 8 ). Moreover, a recent cryo-EM structure of full-length ZipA in complex with FtsZ in lipid nanodiscs ( 20 ) showed that the globular domains of both proteins were closely associated, hinting at additional interactions beyond the canonical FtsZ CTP-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SMALPs once formed are stable, and it is not necessary to supplement all buffers as with conventional detergents, making them technically easier to work with. SMALP purified proteins have successfully been used for both functional [9,12,13] and structural [16][17][18][19] studies. However SMA polymers do not solve all challenges associated with membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…FFEA (Solernou et al ., 2018) represents globular macromolecules such as proteins as continuum objects (Oliver et al ., 2014), and has been previously used to model rotary ATPases, the ZipA/FtsZ membrane protein complexes, and cytoplasmic dynein (Richardson et al ., 2014; Lee et al ., 2019; Hanson et al ., 2020). Within the FFEA framework, proteins are approximated as viscoelastic solids (Wang and Zocchi, 2011) which change shape and explore conformational space under the effect of thermal fluctuations.…”
Section: Methodsmentioning
confidence: 99%